A Hybrid Clean Energy System Based Thermal Solar Technologies - Al-Sharai, A.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Renewable energy, often described as clean energy, is derived from natural sources or mechanisms that are regenerated on a regular basis. Sunlight and heat continue to shine and blow even though their availability is dependent on time and temperature. While capturing nature's power is typically considered a novel technology, it has traditionally been used for transportation, lighting, and other purposes. This study aims to design a clean energy system by using solar and thermal techniques that will generate a hybrid, clean energy continuously from the solar panels and Thermoelectric generators. In this study, we revealed that the design characteristics of the clean energy system's stability after the first conversion of solar and thermal energies can have a big impact on overall efficiencies, which dictate both economics and lifetime. The applications of this system will be highly used in commercial, residential, and industrial sectors. Â© 2021 IEEE.